KEBIJAKAN FORMULASI PEMULIHAN NAMA BAIK KORBAN TINDAK PIDANA PENGHINAAN DAN/ATAU PENCEMARAN NAMA BAIK DALAM PENAGIHAN PIUTANG OLEH DESK COLLECTOR FINTECH P2P LENDING ILEGAL DI INDONESIA - Eliza Della Kanaya; Ade Adhari (Jurnal Hukum Adigama, 2021)
Started from the big amount of complaints related to criminal acts of defamation by Fintech P2P Lending illegal in Indonesia at this time, and realizing that there are obstacles in restoring the good name of victims in the legal system in Indonesia, it is felt that there is a need for legal reform that emphasizes victim recovery. This study examines about the formulation of the good name recovery policy for victims of criminal acts of defamation, especially victims of criminal acts of defamation by illegal Fintech P2P Lending. The type of research used is normative prescriptive which is carried out with a statute approach, comparative approach, and conceptual approach. This research resulted a new concept that can be adapted and applied in Indonesia, namely the form of satisfaction as an alternative in restoring the victim's good name, so that the victim can obtain restitution on his behalf only through the application mechanism, and does not need to file a civil lawsuit. Thus, the victim can get a recovery of his name and restore his social life in society as soon as possible